Synonymic notes on Ctenuchini and Euchromiini (Lepidoptera: Arctiidae) - Grados, Juan (2003)
In this work I present four new synonymies at the species level of Ctenuchini and Euchromiini (Arctiidae) based on examination of primary type material.